Family Business Succession The Final Test of Greatness - Aronoff, C.; McClure, S.; Ward, J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2011)
Helps to prepare for passing the family business on to the next generation. Leaders will learn how to create a succession plan; how to develop opportunities for succession candidates; how to build consensus with the family and leaders on succession plans and finally leaders will learn when and how to let go of their own role in the business.
Keywords: Management; Organization; Planning; Small business; Leadership; Entrepreneurship; Family-owned business enterprises; Management; Organization; Small Business; Business Strategy/Leadership.; Entrepreneurship; Family Business